Prevalence and determinants of gender-based violence among high school female students in Wolaita Sodo, Ethiopia: an institutionally based cross-sectional study - Temesgen Tantu; Sintayehu Wolka; Muluken Gunta; Million Teshome; Hangatu Mohammed; Bereket Duko (BMC, 2020)
Abstract Background Gender-based violence (GBV) often occurs in resource-limited settings such as Ethiopia. It could result in psychological and physical adverse outcomes such as stress, anxiety, depression, unsafe abortion, unwanted pregnancy, and sexually transmitted infections. This study aimed to assess the prevalence and factors associated with gender-based violence among female high school students in Wolaita Sodo, Ethiopia. Methods An institutionally based-cross-sectional study was conducted in Wolaita Sodo, Ethiopia. A total of 604 female high school students were recruited through multi-stage stratified sampling techniques. The gender-based-violence assessment tool, validated by the World Health Organization, was used to assess gender-based-violence and other determinants. The strength of statistical association was measured by adjusted odds ratios and 95% confidence intervals. Statistical significance was declared at p-value < 0.05. Results The lifetime prevalence of GBV, sexual violence, and physical violence were found to be 63.2, 37.2, and 56.3%, respectively. The prevalence of sexual violence before and after joining the current school as well as in the current academic year were 30.5, 37.2, and 22% respectively. Having regular boy-friends (AOR = 2.02; 95% CI:1.07-3.79), being sexually active (AOR = 6.10; 95% CI: 2.49-14.92), having female or male friends who drink alcohol (AOR = 2.18; 95% CI:1.26-3.77), students witnessed their mothers being beaten by their partners or husband (AOR = 1.92; 95% CI:1.19-3.11) and joining public school (AOR = 1.74; 95% CI:1.11-2.76) were significantly associated with gender-based violence. Conclusion The prevalence of gender-based-violence was high. This needs a due concern from governmental, non-governmental and civic organizations as well as other responsible bodies to tackle factors associated with GBV in this study. Further large scale studies incorporating male students are warranted to elucidate the factors associated with GBV in Ethiopia.